A comment on the use of stochastic character maps to estimate evolutionary rate variation in a continuously valued trait (2012)
Phylogenetic comparative biology has progressed considerably in recent years (e.g., Butler and King 2004; Rabosky 2006; Bokma 2008; Alfaro et al. 2009; Stadler 2011; Slater et al. 2012). One of the most important developments has been the application of likelihood-based methods to fit alternative models for trait evolution in a phylogenetic tree with branch lengths proportional to time (e.g., Butler and King 2004; O'Meara et al. 2006; Thomas et al. 2006; Revell and Collar 2009; Beaulieu et al. 2012). An important example of this type of method is O'Meara et al. (2006) “noncensored” test for variation in the evolutionary rate for a continuously valued character trait through time or across the branches of a phylogenetic tree (also see Thomas et al. 2006 for a closely related approach). According to this method, we first hypothesize evolutionary rate regimes on the tree (called “painting” in Butler and King 2004); and then we fit an evolutionary model, specifically the popular Brownian model (Cavalli-Sforza and Edwards 1967; Felsenstein 1973, 1985), in which the instantaneous variance of the Brownian random diffusion process has different values in different parts of the phylogeny (O'Meara et al. 2006).